On-Site Genomic Epidemiological Analysis of Antimicrobial-Resistant Bacteria in Cambodia With Portable Laboratory Equipment - Hirabayashi, Aki; Yanagisawa, Hideji; Takahashi, Hiromizu; Yahara, Koji; Boeing, Philipp; Wolfenden, Bethan; Nov, Vandarith; Lorn, Vichet; Veng, Mom; Ann, Vuth; Darapheak, Chau; Shibayama, Keigo; et al. (Frontiers in Microbiology, 2021)
The rapid emergence of carbapenemase-producing gram-negative bacteria (CPGNB) is a global threat due to the high mortality of infection and limited treatment options. Although there have been many reports of CPGNB isolated from Southeast Asian countries, to date there has been no genetic analysis of CPGNB isolated from Cambodia. Sequence-based molecular epidemiological analysis enables a better understanding of the genotypic characteristics and epidemiological significance of antimicrobial-resistant (AMR) bacteria in each country, and allows countries to enact measures related to AMR issues. In this study, we performed on-site genomic epidemiological analysis of CPGNB isolated in Cambodia using a portable laboratory equipment called Bento Lab, which combines a PCR thermal cycler, microcentrifuge, gel electrophoresis apparatus, and LED transilluminator, along with the MinION nanopore sequencer. PCR targeting of major carbapenemase genes using Bento Lab revealed that two Escherichia coli isolates and one Acinetobacter baumannii isolate harbored carbapenemase genes: blaNDM, blaOXA-48, and blaOXA-23, respectively. The results of phenotypic diagnostic tests for CPGNB, such as the carbapenem inactivation method and double-disk diffusion test using a specific inhibitor of metallo-β-lactamases, were consistent with their AMR genotypes. Whole-genome sequencing analysis using MinION revealed that blaNDM-5 gene was carried on a 93.9-kb plasmid with IncFIA/IncFIB/IncFII/IncQ1 replicons, and blaOXA-181 gene was carried on a 51.5-kb plasmid with the IncX3 replicon in E. coli isolates. blaOXA-23 was encoded in two locations on the chromosome of A. baumannii. Plasmids carrying blaNDM-5 or blaOXA-181 in E. coli were highly structurally identical to plasmids prevalent in Enterobacterales in China and other countries, suggesting that they disseminated from a common evolutionary origin. Our findings demonstrate the potential impact of portable laboratory equipment on AMR bacteria research in hospitals and research centers with limited research facilities, and provide the first glimpse into the genomic epidemiology of CPGNB in Cambodia.